An investigation of the effect of CD, HG and ZN on the growth of two species of blue green algae - Ağlarca, Zeynep. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 1983., 1983)
In this research, effects of three metals, cadmium, mercury and zinc were investigated on two species of blue green algae, Anabaena flos aquae and Gloeocapsa. Cells were grown in sterile medium free of combined nitrogen and under continuous illumination. Metal ions were introduced as chloride salts and different concentrations of the metal ion solutions were used. Absorbance and cell counts were determined for each concentration of the metal ion solution and results were evaluated in terms of these two criteria. Zinc was found to be the most toxic metal for both Anabaena flos aquae and Gloeocapsa whereas the other metals showed inhibitory and stimulatory effects depending on the concentration of the metal ion solution. This showed that effect of the metal whether inhibitory or stimulatory is dependent on the species used and the metal ion itself.
Keywords: Algae.; Cadmium.; Mercury.; Zinc.